Successful Learners of Irish as an L2: Motivation, Identity and Linguistic Mudes - Petit, Kevin (Studia Celtica Posnaniensia, 2016)
This article presents the results of a small-scale research conducted for a master’s thesis on the motivation to learn Irish on the part of university students and members of the Gaelic society An Cumann Gaelach. In the light of questionnaires’ results and interviews, the emphasis is placed on the links between motivation, identity, and potential key moments in learners’ lives. Using an AMTB-type questionnaire (n=45), the author puts to the test Dörnyei’s Motivational Self System theory (2005) in the context of the learning of Irish by looking at the correlation between the motivational intensity of 45 students and six variables (Ideal L2 Self, Ought to Self, Ideal L2 Community, Instrumentality, Parental encouragement, and Role of teachers). The notion of Ideal L2 Self, or the capacity to picture oneself speaking an L2 in the future, clearly appears to be strongly correlated with the respondents’ motivational intensity (r=.75 p<.01), in accordance with Dörnyei’s model. However results concerning extrinsic factors differ from previous research, putting forward distinctive features of the learning of minority languages. The second phase of the research looks at the language learning narratives of three An Cumann Gaelach’s members through the qualitative analysis of three interview transcripts. The results clearly show that time spent in Irish summer colleges are linguistic mudes (Pujolar and Puigdevall 2015), or key-moments, which triggered the interest in the language for the three students interviewed.